Time-resolved molecular dynamics of single and double hydrogen migration in ethanol - Nora G. Kling (Nature Portfolio, 2019)
Chemical dynamics in molecules involve particle migration and bond rearrangement. Here the authors show single and double hydrogen migration in ethanol cations and dications that are generated by using intense laser pulse interaction with a jet of ethanol molecules.